The Effect of Omeprazol in the Treatment of Laryngeal Manifestations of Gastro-oesophageal Reflux - Al-beiruty, Oday Abdelrahman; Rasheed, Ahmed Muhei; Al-Zubaidy, Hayder (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Reflux laryngitis has gain a lot of attention in the last three decades as a possible explanation of idiopathic laryngeal problems.Acid suppressive therapy canbe of use in both the therapeutic and the diagnostic fields.The use of Omeprazole has proved to be of benefit in the diagnosis and treatment of reflux laryngitis.Theresponse to 12weeks course of Omeprazole is considered by many authors to be one of the diagnostic tooles of reflux laryngitis.Aim: Is to study the effect of Omeprazole in the treatment of laryngeal manifestations of gastro-oesophageal refluxPatients and methods: This is a prospective study of 37 patients attending Alkadhimiyah teaching hospital,department of otolalyngology during the period fromApril 2005 to April 2006,complaining of symptoms suggestive of reflux laryngitis.The chief compliant of each patient was taken as a reference for theimprovment.Complete clinical examination was done for each patient as well as videolaryngoscopy.Oesophagogastroscope was done at the department ofgastroenterology. According to the findings seen in those patients,a course of Omeprazole 20mg bid was given for 12 weeks.Re-examenation including videolaryngoscopy was done at6thand12thweeks of treatment.Oesophagogastroscopy was repeated at 12th week of treatment.Resultst: There was symptomatic improvement in the chief complaint and improvement in the videolaryngoscopic findings in 29patients(78.38%)at the end oftreatment course with omeprazole. Conclusion: We found that Omeprazole is effective in producing symptomatic relief in the chief complaint in 78.38% of patients at the end of treatment course.